Cost reduction in farm-based agriculture through increased grower maturity - Chatchawal Telavanich (2018)
© 2015, Kasetsart University. All rights reserved. In agriculture, many methods and systems have been developed to support farming activities focusing on the utilization of knowledge, technology and enforced standards. However, the existing capability of the grower resulting from education is a major obstacle to the full utilization of daily agricultural processes. Consequently, costs and risks associated with agricultural business cannot be effectively managed. This paper presents an alternative sustainable agricultural framework to assist the grower with managing costs and risk management through an improvement in grower capability. A maturity model is applied and developed into a Grower Maturity Model where an increased maturity level translates into better management of costs and risks. Since knowledge plays an important role in capability improvement, a specific learning framework in agricultural business is also developed to represent the relationship between learning and costs and risks. The results show that costs in agricultural processes can be sustainably and effectively reduced through better knowledge and an increase in the capability level of growers. Ten okra growers in Samut Sakhon province exporting to Japan are used as case studies.